Konstruksi Sosial pada Pemberitaan Makan Bergizi Gratis: Analisis Framing Pemberitaan Metrotvnews.Com Periode September 2025 - Luthfia Putri Callista Sari; Prabu Bimantoro; Nadya Chaerunnisa; Harits Hibatullah Sudrajat; Muhammad Rezky Ramadhan (LPPM Institut Pendidikan Nusantara Global, 2026)
The Free Nutritious Food Program (Program Makan Bergizi Gratis or MBG) as a government policy encountered significant challenges since September 2025, triggering intense public scrutiny and media coverage. This study analyzes how MetroTV News.com constructs reality regarding MBG through news framing processes. Using a constructivist qualitative approach, the research involved a population of 214 MetroTV News.com articles with a purposive sample of 10 representative articles from September 2025. Data were collected through content analysis, in-depth interviews with four key informants, and documentary observation. Analysis technique employed Robert N. Entman's framing model across three stages: data reduction, data display, and conclusion drawing based on the Miles and Huberman approach. The study found that MetroTV News.com consistently frames MBG as a fundamental national investment with positive framing strategy during initial reporting, transformation to technical incident framing when crisis emerged, and adoption of a collaborative paradigm with government. Research findings reveal significant gap between media framing and field reality complexity involving infrastructure limitations, human resources constraints, and systemic challenges. The study confirms that mass media plays a crucial role in constructing public policy reality according to institutional ideology and interests, not merely delivering objective information to the public.